PROPOSAL OF A BODY FAT CLASSIFICATION TABLE, USING JACKSON AND POLLOCK (1980) PROTOCOL WITH COM 3 PLAITS, IN FEMALES FROM ACTIVA FITNESS, IN RIO DE JANEIRO - RJ - BRASIL (Fiep Bulletin - online, 2014)
This study has the objective of elaborating a body fat normality table (%F) for specific populations, with similar characteristics to the gym students of the North of Rio de Janeiro - RJ, females, and with ages going from 18 to 55 years old. For this purpose, a data base of physical evaluations from Activa Fitness GYM, from Rio de Janeiro - RJ, was used (N=577, being the age average: 33 years old; standard deviation: 9,57 years; average body fat: 38,62%; and standard deviation of 6,88%), by using Jackson & Pollock Protocol (1980), 3 plaits, for estimating the body fat. The results were all tabulated and statistically calculated by using a descriptive statistics. The table was elaborated with its levels classification going from "Excellent" until "Very Bad", as well as percents and body fat classification. We suggest that further studies are made aiming to widen the amount of data that classify the body composition, based on fat percentage, as well as the elaboration of reference tables for specific areas, making the systematized physical exercise prescription easier.
Keywords: Anthropometry; Normality Table; Skin Plaits